Resistive switching in a metal-insulator-metal device with γ-APTES as the insulator layer. (October 2017) - Lin, Jing-Jenn; Lin, Shih-Hung; Wu, You-Lin
Highlights: The resistive switching characteristics of γ-APTES is reported for the first time. Unipolar resistive switching with a RHRS/RLRS ratio larger than 10 3 is observed. Device stability is improved after adding ZnO nanoparticles into the γ-APTES film. Abstract: Gamma-aminopropyltriethoxysilane (γ-APTES) is an organosilane material commonly used for biomedical sensing. Sensors with a γ-APTES surface layer have been reported for use in pH, DNA, and cell detection. However, no application of γ-APTES on resistive switching random access memory (RRAM) devices has yet been reported. In this paper, we report, for the first time, the resistive switching characteristics of using γ-APTES as the insulator layer in an RRAM device. The resistive switching of the γ-APTES layer embedded with ZnO nanoparticles is also investigated in this work. A unipolar resistive switching characteristic is found when the γ-APTES is employed as an insulator layer in a device with a metal-insulator-metal (MIM) structure. The stability and reliability of the resistive switching characteristics of the device can be improved after adding zinc oxide (ZnO) nanoparticles at the expense of reducing the ratio of the resistance of a high-resistance state (RHRS) to the resistance of a low-resistance state (RLRS).